Metode HIRADC untuk Mengidentifikasi Risiko Kerja di Lapangan A Penumpukan Petikemas PT XYZ - Damanik, Gracia Wiranatalie; Sari, Rizqi Novita (Fakultas Teknik Universitas Tulang Bawang, 2025)
Occupational safety in the container stacking yard of PT XYZ is a primary concern due to the high potential for accidents that can harm both workers and the company. This study aims to identify and assess the risks of occupational accidents in the container stacking yard of PT XYZ and to provide recommendations to improve occupational safety. The HIRADC (Hazard Identification, Risk Assessment, and Determining Control) method was used in this research. The results showed that there are many potential hazards, such as being struck by containers, being caught in heavy equipment, and extreme environmental conditions. Through the HIRADC method, it was found that risks were categorized as low, moderate, high, and very high. Therefore, it is expected that the company can reduce the accident rate and create a safer working environment. Keywords: HIRADC, Container, Occupational Safety, Workplace Safety